RESEARCH TRENDS ON CHARACTER EDUCATION AND INTERACTIVE LEARNING MULTIMEDIA IN ELEMENTARY SCHOOL: A BIBLIOMETRIC ANALYSIS - Mochammad Miftachul Huda; Sapriya Sapriya; Wahyu Sopandi (Jurnal Cakrawala Pendas, 2025)
Using VOSviewer software, this study aims to determine research trends by conducting bibliometric analysis mapping of articles obtained from Google Scholar on the topic of character education and interactive learning multimedia in elementary schools. The keywords "character education," "interactive learning multimedia," and "elementary school" were used to gather article data using the Publish or Perish manager tool. There were 992 articles from 2012 to 2022 in the results. Multimedia interactive learning and network visualization education are not closely related. The most researched topic is interactive multimedia learning with learning motivation. In the meantime, it is difficult to understand how interactive multimedia, elementary school, and character education are related to network visualization. These findings suggest that there is still a dearth of studies on the relationship between multimedia interactive learning and character education in primary schools. This finding indicates that there is a great chance to undertake this research in the future, which will lead to innovative findings.